Capability Gap Analysis in IT Governance for a Logistics Company Using COBIT 2019 - Yusuf, Ahmad; Saputra, Wanvy Arifha; Jamilah, Jamilah (Universitas Bina Darma, 2024)
This paper aims to evaluate the IT governance capability levels within a logistics company using the COBIT 2019 framework, focusing on identifying gaps between the current state (as-is) and the desired state (to-be). The methodology involves an assessment of three key Governance and Management Objectives: stakeholder engagement (EDM05), IT asset management (BAI09), and IT compliance (MEA03). The results indicate that all objectives are currently at capability level 1, highlighting the early stages of implementation and the need for substantial improvement. The study concludes that addressing these gaps through the COBIT 2019 framework will significantly enhance the company’s IT governance, leading to improved operational efficiency, stronger risk management, and better alignment with strategic business goals. These findings provide actionable insights for advancing IT governance maturity, contributing to the long-term success and competitiveness of the company in the logistics sector.